Trade, Human Capital, and Income Risk - Liuchun Deng; Pravin Krishna; Mine Zeynep Senses; Jens Stegmaier (Institute of Labor Economics (IZA), 2021)
In this paper, we empirically assess the causal relationship between trade and individual income risk and study the role that human capital plays in this relationship using a rich, worker-level, longitudinal data set from Germany spanning from 1976 to 2012. Our estimates suggest substantial heterogeneity in labor income risk across workers in different entry cohorts, over workers' life cycles, and across workers with different levels of industry- and occupation- specific human capital. Accounting for entry-cohort effects and age effects, our findings suggest that within-industry changes in imports and exports (per worker) are strongly and causally related to income risk: Imports increase risk and exports decrease risk, and they do so in an economically significant manner. Importantly, we find there to be a complex interplay between human capital and the causal linkage between trade and risk: On average, individuals with higher levels of industry- or occupation-specific human capital experience lower income risk. However, a given increase in net import exposure in an industry increases risk for workers with higher levels of industry tenure more than it does for workers with lower levels of industry tenure. High levels of industry-specific human capital can therefore be costly, from a risk perspective, for workers in highly trade-exposed industries. We find no evidence of such an interaction between risk, industry trade exposure, and occupation-specific human capital.
Keywords: F14; F16; D52; E21; J24; J62; 330; imports; exports; income risk; human capital; Germany